Dysfunction In Isolation: Metaphor Of Personal Urbanisation Experience Through Painting - Zhang, Fan (2024)
This research highlights the dysfunction in isolation as a metaphor in the creation of paintings. A general review of existing artists currently portrays space and objects in the language of painting in their creations. However, their works are more about expressing personal emotions rather than social issues related to isolation. On the other hand, the current painting does not express isolation from the perspective of dysfunction. To establish a theoretical foundation for expressing isolation as a social issue in creative work, analyse the pertinent literature on art and society. Social and emotional problems are gaining ground as urban society and technology advance. The metropolitan population now frequently experiences psychological issues related to isolation. There are several opportunities for studio-based research to add to the corpus of knowledge about creative processes. In this study, I adapt a model of the creative based on the Aesthetico-Action Research model. The primary method for creating a model to produce a sequence of paintings includes observation, reflection, planning, creation, and interpretation. Phase one created a ‘newspaper guy’ and copied it into different works. The ‘newspaper guy’ as a symbol reflects the current state of the urban population. It expresses dysfunction in isolation by representing the connection between the figure and the space. The second phase shows typical urban objects. The absence, overt dysfunction, and excessive approaches are all examples of how the metropolitan populace expresses materialism.